Rohingya Influx and Changing Gender Perception among the Host Community: the Context of Cox’s Bazar of Bangladesh - Mohammad Mohiuddin (Institute of International Studies, 2019)
The paper aims to understand the causes of changing gender perception in Cox’s Bazar district of Bangladesh after the Rohingya influx. Rohingyas have been playing a significant role in the life and attitude of host communities. The study revealed that Rohingya people and their culture are blending with the local people and culture which eventually is affecting the existing hosts’ tradition and practice. Even this blending is restructuring the socio-economic and religion-cultural practices of the host people. On the other hand, NGOs and INGOs are offering jobs to local women and girls. This opportunity though benefiting the stakeholders’ family is ultimately breaking the long-practiced social and religious structure of the society. By and large, the host people are conservative. Women and girls wear veils and they have no practice to work or job by going outside. So, this type of economic, societal, and cultural empowerment of women and girls sometimes contrasts with religious and social long drilled practices in the host area. Further, families who could not afford to manage any job in the camp feel frustrated and sometimes play a negative impression on the women's and girls’ mobility and job. Hence, the key question of the article is to know why the perception of gender in the host area is changing after the Rohingya arrivals. Methodologically, this is explorative research that followed the qualitative method instrumented with the Case studies, Key Informant Interviews (KIIs), and Focus Group Discussions (FGDs). The paper has also endeavored to address the changing nature of women’s empowerment and gender dimension in the host area that occurred after the Rohingya influx which is not explored yet. Therefore, this study can be a fairy source for posterior researchers.